Kesulitan Belajar Siswa Pada Mata Pelajaran Geografi Kelas X IIS 1 SMA Negeri 1 Watopute - Leniawati; Surdin; Andrias (Jurnal Penelitian Pendidikan Geografi, 2023)
Learning difficulty is the inability of a student to master a subject matter optimally in a predetermined time due to several factors that influence it. The aims of this study were: 1) to describe the description of student learning outcomes in Geography class X IIS 1 Senior High School 1 Watopute; 2) to analyze what material is difficult for students to understand in the subject of Geography for class X IIS 1 Senior High School 1 Watopute, and; 3) to describe the factors that cause learning difficulties in the subject of Geography class X IIS 1 Senior High School 1 Watopute. This research is a qualitative descriptive study. The results of the study showed that: 1) student learning outcomes, namely some students in class X IIS 1 did not reach the minimum completeness criteria in Geography; 2) The material that is difficult for students to understand in the subject of Geography for class X IIS 1 students is the material on the Characteristics of the Layers of the Earth's Atmosphere; and 3) factors that cause geography learning difficulties, namely internal factors (student interest and student motivation) and external factors (parents' work, parental income, student learning needs, the presentation of material by the teacher is less attractive, the use of monotonous learning methods, the use of less than optimal learning media, and limited school facilities and infrastructure).